KAJIAN LITERATUR PENGARUH SENYAWA BIOAKTIF TANAMAN HERBAL TERHADAP INHIBISI ENZIM Α-GLUKOSIDASE DAN Α-AMILASE SEBAGAI UPAYA PENCEGAHAN DIABETES MELITUS - Nadia Dwi Salsabila; Yuda Frans Aresco Saragih; Selli Ronatio Sinaga; Melisa Theoria Simanjuntak; Moses Christanto Siahaan; Ida Duma Riris (STKIP Subang, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia resulting from impaired insulin secretion, impaired insulin action, or both. One strategy for preventing postprandial hyperglycemia involves inhibiting the enzymes α-amylase and α-glucosidase, which play a key role in carbohydrate digestion. The objective of this study is to investigate the effects of bioactive compounds from medicinal plants on the inhibition of α-amylase and α-glucosidase enzymes as a preventive measure against diabetes mellitus. A literature review was conducted, in which various scientific articles from Google Scholar, ScienceDirect, SpringerLink, MDPI, Wiley Online Library, and ResearchGate were collected, analyzed, and evaluated. The results of the study indicate that several medicinal plants, such as Swietenia mahagoni, Annona muricata, Moringa oleifera, Gastrodia elata, and Zingiber cassumunar Roxb. contain bioactive compounds such as phenols, flavonoids, limonoids, alkaloids, tannins, saponins, quinones, and triterpenoids, which can inhibit the activity of the enzymes α-amylase and α-glucosidase. Mahogany seed extract exhibited 77.52% inhibition of α-amylase at a concentration of 500 µg/ml, while bangle extract demonstrated an inhibitory effect on α-glucosidase with an IC₅₀ value of 98.31 µg/ml. These findings suggest that bioactive compounds from herbal plants have the potential to be developed as natural antidiabetic agents by inhibiting digestive enzymes, thereby helping to control blood glucose levels.